Bibliometric analysis for the identification of factors of innovation in the food industry (2015)
The article below discusses the purpose of identifying the main factors of innovation presented in specialized literature about the food industry. For its development, a bibliometric exercise aimed at analyzing scientific articles in the field was conducted. Based on the results, it drew the conclusion that the main factors for innovation in the food industry are associated with channels of communication and participation in the production process of customers, suppliers or public or private institutions (such as universities or research centers). Thanks to the links created among stakeholders, knowledge and information is shared mainly about the quality of life, nutrition and production efficiency, thus impacting product development, changes to the existing offer or in production processes. In this perspective, innovation in the industry subscribes to "Open Innovation" where "Co-innovation" and "Co-creation" are key for the terms of trade and for the participation of stakeholders